(untitled) (Yesterday & Today Journal for History Education in South Africa and abroad, 2025)
Despite significant educational reforms by post-apartheid South Africa aimed at democratising and decolonising its education system, a concerning exclusion persists: Black intellectuals, particularly the 1950s Drum generation and their contributions to the liberation struggle, remain marginalised within the knowledge base of the post-apartheid school history curriculum. Using epistemic coloniality and epistemic disobedience as the first aspects of our theoretical framing, we investigated this peripheralisation. Additionally, we also used historical significance and epistemic pluriversality to frame our argument for the inclusion of the 1950s Drum generation’s contributions to the South African liberation struggle in the knowledge base of the school history curriculum, given the significant role they played. Methodologically, we employed a qualitative case study design underpinned by a critical paradigm, with critical discourse analysis as our tools of analysis. We conclude that since the 1950s were formative years for enacting and resisting colonial-apartheid policies, teaching about the 1950s Drum generation would enable both history educators and their learners to appreciate artistic, cultural, and literary contributions to the liberation struggle. This would also reveal to them that liberation was shaped not solely by political actors, but equally by cultural and literary figures who spoke truth to power.